The Psychological Determinants toward The Value of Healthy Food among Type 2 Diabetes Mellitus Consumers - Nurliza, Nurliza (Universitas Airlangga, 2022)
Adults and middle-aged food consumers are the most at risk of type 2 diabetes, and these consumers are varied across demographics. While few and fragmented studies are associated with psychological determinants and healthy food value through food choices. Few consumer roles are involved in research for business success. The psychological determinants toward the value of healthy food for type 2 diabetes consumers used consumer behavior and psychological theories of consumer choices. An associative method with purposive sampling was conducted from 165 adults and middle-aged consumers with type 2 diabetes using Structural Equation Modeling/SEM. The finding showed that the belief, attitude, and mood affected the value of healthy food through food choice, but not psychological distress. The attitude had the greatest effect on food choice and toward the value of healthy food, and the causal of the highest result effect of life experiences. The belief was directly affected food choice and value, and the causal for the highest effect of self-consciousness and health maintenance. The mood negatively affected both food choice and value of healthy food mood and the causal for the smallest effect of health maintenance. The food choice affected the values of healthy food. Life experience was the most direct and indirect effect of food choice and self-consciousness was the most direct effect of the value of healthy food. Some highlights of this study were (i)market segmentation and segmentation variable; (ii)social marketing; (iii)mass media campaign by considering attitude, belief, and mood; and (iv)human capital management strategy with targeted audiences.